Pengaruh Diskon dan Cashback terhadap Keputusan Pembelian Konsumen di E-Commerce (Studi kasus shopee) - Sintya Enjel; Fadilla Nurul Istiqomah; Illiana Illiana; Nurul Lestari; Agung Rizki Putra (Jurnal Ekonomi Manajemen Akuntansi, 2025)
This study aims to analyze the effect of discounts and cashback on consumer purchasing decisions on the Shopee e-commerce platform. Using a quantitative approach, data were collected through questionnaires distributed to 100 respondents who are active Shopee users. The results of the analysis show that discounts have a positive and significant effect on purchasing decisions, where consumers tend to be more interested in shopping when offered attractive discounts. In addition, cashback programs have also been shown to increase product appeal and contribute significantly to purchasing decisions. This study concludes that both discounts and cashback simultaneously influence consumer purchasing decisions, with important implications for e-commerce marketing strategies to increase loyalty and competitiveness in the market.